Effect of Dielectric Environment on Excitonic Dynamics in Monolayer WS2. Issue 23 (22nd October 2019) - Fu, Yang; He, Dawei; He, Jiaqi; Bian, Ang; Zhang, Lu; Liu, Shuangyan; Wang, Yongsheng; Zhao, Hui
Abstract: An experimental study on the effect of hexagonal boron nitride ( h ‐BN) underlay and cap layers on excitonic dynamics in monolayer WS2 is reported. A monolayer WS2 flake is fabricated by mechanical exfoliation. By using a dry transfer technique, three regions of the sample are obtained: WS2 directly on SiO2, WS2 on h ‐BN, and WS2 sandwiched by two h ‐BN flakes. Photoluminescence measurements show higher yield and narrower linewidth of the h ‐BN/WS2 / h ‐BN region. Transient absorption measurements reveal that the top h ‐BN layer enhances the exciton formation, prolongs the exciton lifetime, and slightly affects the exciton–exciton annihilation. By performing spatially resolved transient absorption measurements, exciton diffusion coefficients of about 100, 40, and 26 cm 2 s − 1 for the regions of WS2, h ‐BN/WS2, and h ‐BN/WS2 / h ‐BN, respectively, are obtained. The suppression of exciton diffusion by h ‐BN is attributed to the additional phonon scattering mechanisms introduced by h ‐BN, which decreases the exciton mean free path and thus the diffusion coefficient. The findings provide useful information for designing and understanding the effect of h ‐BN layers interfacing with 2D semiconductors. Abstract : The effect of dielectric screening by hexagonal boron nitride cap and under layers on excitonic dynamics of monolayer tungsten disulfide is revealed by femtosecond transient absorption microscopy. The boron nitride layer enhances the exciton formation, prolongs the exciton lifetime, suppresses exciton in‐plane diffusion, and has minimal effect on exciton–exciton annihilation.